Predictors of Uncontrolled Seizure in Children Presenting in Tertiary Level Hospital in Nepal: A Prospective Study - Shrestha, Merina; Bajracharya, Luna (Journal of Institute of Medicine Nepal, 2021)
Introduction About one third of the children with seizure do not achieve complete seizure control. We aimed to find the predictive factors for uncontrolled seizure in children. Methods This prospective study was conducted from October 2018 to September 2020 at Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Children aged 12 months to 16 years with seizure and who were under regular follow up visits for at least once in past 3 months time were included and followed up for one year. Uncontrolled seizure was defined when seizure frequency was 2 or more in a year during the study period. Various factors were analyzed and when they were significantly different between the groups on bivariate analysis using the Chi square test, they were further analyzed with binary logistic regression model to find out the true predictors. Results Total of 110 children were enrolled. Forty children (36.4%) had their seizure onset before one year of age. About one third of patient had family history of seizure. The most common type of seizure was generalized type (60%). Of the total, 56% had uncontrolled seizure. Three true predictors of uncontrolled seizure were found. They were (i) age of onset before 12 months of age (OR 2.94; 95% C.I 1.32- 6.55), (ii) abnormal findings in neuroimaging (OR 26.5; 95% C.I 8.72-80.07) and (iii) frequency of seizure (OR 40.9; 95% CI 9.05-184.9). Conclusion Seizure onset in infancy, abnormal neuroimaging findings and frequent seizure are predictors for uncontrolled seizure in children. Thus, we suggest that these factors be considered while managing the children with seizure.